Influence of mergers and acquisitions on the quality of service in bus transportation: Research after company acquisition - Saša Ilić; Mladen Pancić; Ivan Kristek (Ekonomski Vjesnik, 2019)
Today’s environment in which the companies are doing business is dynamic and unpredictable. The companies are therefore forced to implement changes in business processes. Changes can be related to human resources, new technological processes, openness to new markets and other factors. One of the big changes are acquisitions or mergers of companies. Mergers and takeovers of companies have been present in the business world for a long time, and their influence on the economy is significant. The most common motive is increasing the competitive advantage, improving financial indicators, creating added value to service, etc. This paper looks into the influence of mergers, i.e. acquisitions in bus transportation on the quality of service provided. It is the first research related to the quality of service after the acquisition of the companies Autotrans d.o.o. and Autoprometno poduzeće d.d. by Arriva Hrvatska, which was carried out in 2018. Acquisitions and mergers are an opportunity for organisations to position themselves on the market and improve their performance, but also a huge challenge for the management. Such a process requires effort and time to bring it to successful completion. That also includes continuous work on ensuring the quality of provided services, i.e. the implementation and maintenance of tangible and intangible elements of the service, which will in the end secure success on the market.